Techno-economic analysis of a solar drying plant using scheffler dish technology and eutectic PCM mixtures for thermal energy storage system - Claude Ziad El-Bayeh (17542284) (2025)
Solar drying for food products is a cost-effective and environmentally friendly technology that is widely used in low-temperature drying processes. In this paper, we design a Solar Drying Plant (SDP) based on Scheffler Dish technology with a Thermal Energy Storage (TES) system. The main goal is to dry 200–250 kg of sliced food products by blowing hot air. The year-round performance and techno-economic analysis of the designed system is evaluated. To reduce the initial investment cost of the designed system, ten different eutectic mixtures of phase-change materials (PCM) are studied and compared, and the most suitable material is selected for the study considering many economic factors, such as, net present worth, payback period, life cycle cost savings, and interest rate of return. Results show that the ternary eutectic mixture of NaOH (85.8 %) - NaCl (7.8 %) - Na2CO3 (6.4 %) is the most profitable PCM among others, in which it resulted in a minimum investment cost of $25,428, minimum annual running cost of $4326, a higher annual savings of $8092, and a minimum CO2 emission. Other Information Published in: Energy 360 License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.energ.2025.100025